PENGARUH SELF ASSESSMENT SYSTEM TERHADAP KEPATUHAN MEMBAYAR PPN OLEH PENGUSAHA KENA PAJAK DI KOTA LHOKSEUMAWE (Survei pada Bengkel Sepeda Motor di Kota Lhokseumawe) - Amidiyah Amidiyah; Edi Zulfiar; Neo Agustina (LPPM STIE Lhokseumawe, 2017)
This study on the effect of Self Assessment System to compliance by employers to pay PPN taxable in Lhokseumawe. The purpose of this study is to determine the effect of the Self Assessment System to compliance by employers to pay PPN taxable in Lhokseumawe. The data used in this study are primary data by dividing questionnaires to 58 employers taxable motorcycle repair shop in Lhokseumawe were used as samples. The data processing is done with the help of a simple linear equation model SPSS version 16. The results showed that: Self Assessment System have a relationship (correlation) is very strong compliance by employers to pay PPN taxable in Lhokseumawe. Self Assessment System has the ability to explain its influence to pay PPN compliance by employers taxable in Lhokseumawe. Self Assessment System significantly influences compliance by employers to pay PPN taxable in Lhokseumawe.